2023
DOI: 10.1177/02698811231212151
|View full text |Cite
|
Sign up to set email alerts
|

Value-based decision-making predicts alcohol use and related problems in young men

Johannes Petzold,
Angela Hentschel,
Hao Chen
et al.

Abstract: Background: Alcohol consumption is a leading cause of morbidity and mortality worldwide, disproportionately affecting young men. Heavy episodic drinking is particularly prevalent among men, with this behavior peaking between the ages of 20 and 24. Aims: We sought to identify dimensions of decision-making in men that would predict the development of hazardous alcohol use through emerging adulthood. Methods: This prospective observational study profiled value-based decision-making in 198 healthy men at age 18 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…However, our findings support the current literature on value-based decision-making and the maladaptive processes associated with impulsive choosing. 50,51 We generally showed that reward is encoded more than risk, PE more than VE , and that more impulsive choices are characterized by more widespread and rigid VE s.…”
Section: Discussionmentioning
confidence: 86%
“…However, our findings support the current literature on value-based decision-making and the maladaptive processes associated with impulsive choosing. 50,51 We generally showed that reward is encoded more than risk, PE more than VE , and that more impulsive choices are characterized by more widespread and rigid VE s.…”
Section: Discussionmentioning
confidence: 86%
“…Additionally, two studies reported the association of T. gondii with SB in people with significant alcohol levels in their blood. Alcohol intoxication could serve as a trigger for the transition to suicidal behavior, as alcohol itself could influence decision making, interfering with the effect of toxoplasmosis [117]. Another limitation refers to the lack of information on the socioeconomic status of the included individuals, which might also be a potential confounder.…”
Section: Toxoplasmosismentioning
confidence: 99%